Use the Commutative Property to determine the missing step in proving the equivalence of 12a+10+a=10+a+12a.

Step 1: [missing]

Step 2: 10+13a=10+13a

Step 3: The expressions are equivalent because they both equal the same value.

(1 point)
Responses

12a+10+a−10=10+a+12a−10
d plus 10 plus a equals 10 plus a plus d

12a+10+a−a=10+a+12a−a
d plus 10 plus a equals 10 plus a plus d

12a+10=10+12a
d plus 10 plus a equals 10 plus a plus d

10+12a+a=10+13a

1 answer

To use the Commutative Property to determine the missing step in the proof of the equivalence \(12a + 10 + a = 10 + a + 12a\), we should rearrange the terms in the expression.

The missing step can be:

Step 1: \(12a + a + 10 = 10 + a + 12a\)

From here, rearranging the left side using the Commutative Property results in:

Step 2: \(10 + 13a = 10 + 13a\)

So the correct missing step is:

12a + a + 10 = 10 + a + 12a.

Therefore the option to choose is:

10 + 12a + a = 10 + 13a.